PERANCANGAN SISTEM INFORMASI KEARSIPAN SURAT MASUK DAN SURAT KELUAR BERBASIS MULTIUSER - Lisnawanty Lisnawanty (Universitas Bina Sarana Informatika, 2014)
According to Law No. 43 of 2009 on Archival Records stating that archival is a recording of activities/events in various forms and media in accordance with the development of Information and Communication Technology. The importance of records management incoming mail and outgoing mail-based computer so that the information can be processed with relevant, timely and accurate, so as to minimize the obstacles that occur when a letter is managed conventionally. The design of information systems archive incoming and outgoing mail is designed multiuser easier for users (Staff Operations, Director, and Section) in the management of documentation incoming mail and outgoing mail writing, disposition letter, letter of data search, presentation of information, and may be evidence or reference history archives, so as to support the performance of operational staff or archivists in managing data incoming and outgoing mail.Keywords: archival information system, incoming mail, outgoing mail, multiuser.